2012
DOI: 10.1155/2012/398640
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Reverse Migration Becomes Transparent with Zebrafish

Abstract: The precise control of neutrophil-mediated inflammation is critical for both host defense and the prevention of immunopathology. In vivo imaging studies in zebrafish, and more recently in mice, have made the novel observation that neutrophils leave a site of inflammation through a process called neutrophil reverse migration. The application of advanced imaging techniques to the genetically tractable, optically transparent zebrafish larvae was critical for these advances. Still, the mechanisms underlying neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 77 publications
(128 reference statements)
1
36
0
Order By: Relevance
“…In view of this, we first addressed the expression of both zebrafish cxcl8 at different time points in 3 dpf Tg(mpx:gfp)i114 larvae under acute inflammatory conditions using quantitative PCR (qPCR). In this study, we made use of the tail fin transection model, a validated model to investigate acute inflammation (16)(17)(18)(19)(20)(21)(22)(23). We found that the mRNA levels of cxcl8-l1 and cxcl8-l2 were significantly increased in injured tail fin tissue and peaked at 1 hpw (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In view of this, we first addressed the expression of both zebrafish cxcl8 at different time points in 3 dpf Tg(mpx:gfp)i114 larvae under acute inflammatory conditions using quantitative PCR (qPCR). In this study, we made use of the tail fin transection model, a validated model to investigate acute inflammation (16)(17)(18)(19)(20)(21)(22)(23). We found that the mRNA levels of cxcl8-l1 and cxcl8-l2 were significantly increased in injured tail fin tissue and peaked at 1 hpw (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…Additionally, the optical transparency of zebrafish and the development of fluorescent cell-specific transgenic lines have enabled the in vivo study of leukocyte biology (14,15). Zebrafish neutrophils have now been extensively studied in inflammation (16)(17)(18)(19)(20)(21)(22)(23), infection (24)(25)(26)(27), and tumor progression (28)(29)(30).…”
mentioning
confidence: 99%
“…Resolution of inflammation is an essential step during wound repair (Starnes and Huttenlocher, 2012). In some human diseases, like pyoderma gangrenosum, inflammation fails to resolve, contributing to chronic wounds and tissue damage (Powell et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil removal is commonly thought to occur exclusively through engulfment by macrophages. 9,10 However, emerging results from live imaging of embryonic zebrafish suggest that neutrophils can also reverse migrate away from sites of inflammation 11-14 , a process that can be modulated by various mediators and compounds. 15,16 …”
Section: Introductionmentioning
confidence: 99%